Digital skill level and perceived quality in the use of food delivery apps - Donzelli, Juliana Ribeiro Garcia; Vils , Leonardo (Revista de Administração da UFSM, 2025)
Porpouse: The objective of this research is to examine the relationship between digital skills and satisfaction in the use of food delivery apps, when mediated by perceived quality. This quality is influenced by high demand and, consequently, by complaints and dissatisfaction with the use of these apps during the global crisis of the Covid-19 pandemic. Design/method/approach: A structural model was developed and empirically tested, based on digital skills and satisfaction with food delivery apps, mediated by quality, using data collected from 170 Brazilians between January and February 2023. Findings: The results showed that respondents only demonstrate satisfaction with food delivery apps if they perceive the quality of the apps, and for this to happen, the user must have digital skills. In other words, there is no satisfaction without perceived quality, and for quality to be perceived, digital skills are necessary. Originality/value: A first and second-order model encompassing digital skill level, perceived quality, and satisfaction can offer significant contributions to the literature. This is particularly true when considering digital skill level as a second-order construct, which can be reflective-formative or reflective-reflective. This construct is composed of dimensions such as platform navigation, functional use, creative skills, online problem-solving, social media engagement, and operational aspects. This approach enables a more comprehensive and accurate representation of the concept, overcoming the common limitation in the literature that often treats it as a one-dimensional construct. From a practical standpoint, this model provides valuable insights for organizations, digital platforms, educational institutions, and governmental bodies that need to adapt their services to audiences with varying levels of digital literacy. Furthermore, it deepens the understanding of user experience by demonstrating that perceived quality and satisfaction do not solely depend on product or service characteristics, but also on the individual’s digital competencies.